Role of Mutravegadharana (Suppression of Urine Urge) in the causation of Mutravahasroto Dushtijanya Vikaras (Urinary Tract Diseases) – An Appraisal - Prakash, Jyoti; Baghel , A S; Kamble, Shubhangi; Chinthala, Rajkumar; Shruti (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda is an ancient medical system that emphasizes holistic health. Indian sages described a healthy human lifestyle thousands of years ago. Ayurveda aims to maintain healthy people’s health and to cure diseases. Vegadharana has been identified as a major cause of illness and disease. Mutra Vegadharana is one cause of Mutravaha Srotas Vikaras. Mutravaha Srotas Vikaras are conditions that affect the kidneys, ureters, bladder, and urethra, as well as other parts of the urinary tract. Mutrakrichchhra (Urinary Tract Infection), Mutraghata (Obstructive Uropathy either mechanical or functional), Prameha (Obstinate Urinary Disorders including diabetes) are some common diseases of the urinary system. It is estimated that 150 million UTIs occur yearly on a global basis. Ignorance of these diseases can lead to some serious renal complications. Suppression of urine urge prevents the passage of urine; keeping it inside the bladder for too long creates an environment where such diseases can develop. Here, an effort is made to explain how Mutra Vegadharana and Mutravaha Srotas Vikara are related.